Assessment of spinel-type mixed valence Cu/Co and Ni/Co-based oxides for power production in single-chamber microbial fuel cells. (15th October 2016) - Ortiz-Martínez, V.M.; Salar-García, M.J.; Touati, K.; Hernández-Fernández, F.J.; de los Ríos, A.P.; Belhoucine, F.; Berrabbah, A. Alioua
Abstract: Microbial Fuel Cell (MFC) is one of the most promising technologies for bioenergy production from wastewater. The improvement of MFC efficiency requires the replacement of noble catalysts for the cathode reaction by low-cost and effective materials. Thus, this work aims at studying the use of transition spinel metal-based oxides as potential cathode catalysts in these devices. Several spinel cobalt-based oxides doped with copper and nickel were synthesized by thermal decomposition at different Cu:Co and Ni:Co atomic ratios and assessed mainly in terms of power performance and chemical oxygen removal (COD) in single-chamber MFCs. The particle size and chemical composition of these catalysts were characterized by TEM and XRD analyses prior to MFC set-up. Among the compounds tested, the nanostructured copper-doped cobalt oxide with chemical formula (Cu0.30 Co0.70 )Co2 O4 offered the highest maximum power output of 567.58 mW m −2, which accounts for over 87% of the total power generated by Pt-sprayed cathodes. Cu0.72 Co2.28 O4 also reached a significant power density of 354.92 mW m −2 . Spinel oxide-based MFCs achieved COD removal values of approximately 56% after 240 h of operation. Finally, this work compares the performance of the spinel oxides investigated with other transition metal based catalysts reported in the literature. Graphical abstract: Highlights: Application of spinel Co oxides by decomposition method in MFCs. Spinel oxides doped with Cu and Ni as catalysts in single-chamber MFCs. Nano-oxides (Cu0.30 Co0.70 )Co2 O4 and Cu0.72 Co2.28 O4 offer the highest performances. (Cu0.30 Co0.70 )Co2 O4 achieved 87% out of the power output reached by platinum.